Unveiling the therapeutic potential of Ficus benghalensis: A review of its traditional uses, phytochemistry, and pharmacological activities - Hassan, Ali; Usman, Ali; Ghazali, Muhammad Hussain (Journal of Pure and Applied Agriculture, 2025)
Traditional medicinal systems offer a valuable repository of knowledge for identifying biologically active plant species. Plants have been a cornerstone of traditional and modern medicine due to their diverse bioactive compounds. Among the plethora of medicinal plants, the Ficus genus holds particular importance, and Ficus benghalensis stands out for its sacred status and extensive applications. A species revered in Ayurveda and Siddha, it has been extensively utilized in South Asian traditional medicinal systems. Its common name, the Banyan tree, reflects its deep cultural and medicinal roots in the region. This review comprehensively examines the phytochemical profile and pharmacological activities of various plant parts, with a particular emphasis on the fruit's potential therapeutic applications. The plant's phytochemical constituents, including phenolics, flavanols, and terpenes, contribute to its multifaceted pharmacological properties. Advanced analytical techniques have identified key compounds such as bergenin, leukocyanidin, and β-sitosterol, which are largely responsible for its observed bioactivity. These properties encompass antioxidative, antimutagenic, and antidiabetic effects, as well as anti-inflammatory, antitumor, and antiproliferative activities. F. benghalensis exhibits wound healing, antimicrobial, and anti-helminthic properties, along with anticancer and hair growth promotion effects. Its immunomodulatory, hepatoprotective, and antistress activities further underscore its medicinal value. Despite its extensive traditional use, a significant gap remains between empirical applications and validated scientific evidence for many of its purported benefits. Future research directions may involve investigating unexplored pharmacological aspects of F. benghalensis, potentially leading to the development of innovative therapeutic agents. Elucidating the plant's mechanisms of action and optimizing its bioactive compounds through modern drug delivery systems could significantly enhance its therapeutic potential.